The Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Keterampilan Berkomunikasi Lisan Siswa Kelas III Sekolah Dasar - Styo Mahendra Wasita Aji; Yuniawantika (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
Online learning carried out in class IIIA of SDN Experimental 1 Malang City encountered problems in developing students' communication skills. The purpose of the study is to describe the application of the discovery learning model, and describe the improvement of students' oral communication skills with the application of discovery learning. The chosen method is classroom action research to improve the quality of learning through 2 cycles with 4 meetings. The results of the cycle 1 study showed that students' oral communication skills with discovery learning improved compared to the results when pre-action without the application of the model. Meanwhile, the results of students' communication skills again increased learning discovery learning at the end of cycle 2. Thus, the application of the discovery learning model can improve students' oral communication skills.